Kenya Economic Update, October 2019 : Securing Future Growth - Policies to Support Kenya’s Digital Transformation - World Bank Group (World Bank, Nairobi, 2019)
Kenya continues to experience steady economic growth, with real GDP expanding on average by about 5.6 percent over the last five years (2014-2018). In 2019, however, economic activity has softened primarily due to lower agricultural output and weak private sector investment. As a result, the World Bank projects Kenya’s growth at 5.8 percent for 2019 and settling at around 5.9 percent over the medium term. The weakening of private investment partly reflects crowding out from widening fiscal deficits and relatedly limited access to credit by the private sector (growing by about 6.3 percent in August 2019). Against this backdrop, it is my great pleasure to present the twentieth edition of the World Bank’s Kenya Economic Update.